Pembuatan Video Panduan Layanan Perpustakaan di Perpustakaan Universitas Negeri dalam bentuk Motion Graphic - Luqyana Nada Masar; Marlini Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
Abstract This paper discusses "Making Video Service Guide in Padang State University Library in the form of Motion Graphic". This paper is to introduce the services of the Padang State University Library to users. Describe the making of a video library service in Padang State University library in the form of motion graphics. The research method used in the discussion of this paper is descriptive. Descriptive method seeks to make a description, discuss systematically, factual and accurate about facts, facts, traits and relationships between phenomena investigated by observation and interview. In the first discussion chapter, the user needs to make a library service video at Padang State University in the form of motion graphics that are designed and implemented for users, specifically for students and Padang State University. In its use, users are expected to get information about services in the Padang State University Library. Second, start making video library services in Padang State University Library as follows: (1) concept or concept, (2) design or drawing, (3) material collection or material collection, (4) Assembly or collection, (5) testing or test, (6) distribution or distribution. Third, the trial results of the Padang State University library video products in the form of motion graphics conducted to the Head of the Padang State University Library gave a pretty good response to provide information to the users and also gave a response given by the librarian from the State University of Padang. Results of product trials to users so know the hours of operation of the library and also the use of existing services at the Padang State University Library.Keywords: service, library, motion graphic